(untitled) (Journal of Educational Sciences, 2026)
The article addresses issues related to the increasing demand in contemporary society for specialists capable of effective interaction in a multicultural environment. The importance of forming intercultural competence as one of the key tasks of the education system is emphasized. The aim of the study is the theoretical and practical substantiation of the development of intercultural competence among college students. Approaches of both domestic and international researchers are analyzed, taking into account the interdisciplinary nature of the concept of “intercultural competence.” Despite the considerable number of studies in pedagogy, insufficient elaboration of the issue of forming intercultural competence specifically among college students is demonstrated. One of the factors hindering interaction between representatives of different cultural traditions is the low level of intercultural competence among future specialists in various professional fields. The authors elucidate the essence of the concepts “competence” and “intercultural competence”, and describe their structure and key components. The research methods included the analysis of scientific literature and diagnostic methods for determining the level of intercultural competence among students. The experiment involved 90 students from the «College of Catering and Service» in Astana. Indicators and criteria for assessing the components of intercultural competence among college students were identified. In the conclusion of the article, the results of the experimental work aimed at developing intercultural competence among college students are presented. Conclusions were drawn, and method-ological recommendations aimed at increasing the effectiveness of this process were proposed. Keywords: competence, cultural competence, intercultural competence, college students.